Phytochemical and Pharmacological Comparison of Wild and Micropropagated Methanolic Leaf Extracts of Ulmus wallichiana - Shahri, Nidha Zahoor; Manzoor, Munisa; Shah, Mohammad Umar; Rather, Gulzar Ahmed; Kaloo, Zahoor Ahmad; Roy, Arpita; Raja, Vaseem (Asian Journal of Chemistry, 2026)
This study compared the phytochemicals, antioxidant, antibacterial, anti-inflammatory and cytotoxic activities of wild (WUWE) and micropropagated (MUWE) Ulmus wallichiana methanolic leaf extracts. Direct shoot regeneration was successfully optimised using DKW medium along with 8.8 µmol/L BAP and 5 µmol/L PCIB, resulting in high shoot induction (85.65 ± 0.20%), shoot number (7.46 ± 0.22) and shoot length (5.35 ± 0.23 cm). Phytochemical analysis revealed that MUWE contained higher levels of alkaloids, flavonoids, phenols and carbohydrates than WUWE. MUWE exhibited higher levels of phenolics and flavonoids compared to WUWE. Antibacterial screening showed effective inhibition by both extracts against E. coli, P. aeruginosa, S. aureus and E. faecalis, with MUWE exhibiting slightly superior activity. Antioxidant potential, assessed using DPPH and ABTS assays, indicated stronger free radical scavenging by MUWE (IC50 23.81 and 20.66 µg/mL) compared to WUWE (IC50 30.72 and 29.83 µg/mL). MUWE also displayed higher anti-inflammatory activity (IC50 26.77 µg/mL) than WUWE (IC50 35.89 µg/mL). The cytotoxicity against HCT-116 colon cancer cells revealed enhanced antiproliferative activity by MUWE (IC50 75.24 µg/mL). Phase contrast microscopy confirmed these effects, showing cell rounding, fragmentation and loss of confluence with MUWE treatment. These findings suggest that micropropagation enhances both the phytochemical richness and therapeutic efficacy of U. wallichiana.